Protein and energy requirements of castrated male Saanen goats - Ferreira, Angela Cristina Dias [UNESP]; Yanez, Enrique Alejandro [UNESP]; Medeiros, Ariosvaldo Nunes de [UNESP]; Resende, Kleber Tomas de [UNESP]; Pereira Filho, J. M. [UNESP]; Machado da Rocha Fernandes, Marcia Helena [UNESP]; Almeida, Amelia Katiane [UNESP]; Molina de Almeida Teixeira, Izabelle Auxiliadora [UNESP] (Elsevier B.V., 2015)
A comparative slaughter trial was conducted to determine the energy and protein requirements for growth of castrated male Saanen goats weighing from 20 to 35 kg body weight (BW). Regarding maintenance requirements, 36 castrated male Saanen goats with an initial BW of 20.7 +/- 0.5 kg, and aged 3.3 1 +/- 0.6 months, were used. Nine animals were randomly chosen and slaughtered at the beginning of the experimental phase (BW of 21.0 +/- 0.4 kg), representing the baseline (BL) group. The 27 remaining castrated male goats were pair-fed into nine groups (blocks) of three animals each, fed either ad libitum or restricted to 30 or 60% of ad libitum intake. A group was slaughtered when the animal fed ad libitum reached 35 kg BW. Regarding requirements for gain, 27 castrated male Saanen goats were fed ad libitum and nine were slaughtered at 21.0 +/- 10.4 kg BW, nine at 27.7 +/- 0.5 kg BW and nine-at 35.1 +/- 0.3 kg BW. The BL and ad libitum-fed animals used to determine maintenance requirements were also used to estimate gain requirements. The net energy (NE) requirement for maintenance was 261.5 kJ/kg(0.75) BW. The metabolizable energy (ME) requirement for maintenance was 404.2 kJ/kg(0.75) BW; therefore, the partial efficiency of use of ME for NE was 0.65. The minimal endogenous N losses were 262 +/- 48.4 mg N/kg(0.75) empty BW (EBW), corresponding to a net protein requirement for maintenance of 1.39 +/- 0.257 g/kg(0.75) BW. The net energy for gain increased by approximately 40% (from 12 to 17 MJ/kg EBW gain) and the net protein for gain slightly decreased by 3% (from 166 to 160 g/kg EBW gain) as the BW increased from 20 to 35 kg. Our study contributes to the improvement of goat nutrition because it provides estimates of the protein and energy requirements of castrated male Saanen goats.
Keywords: Body composition; Comparative slaughter; Efficiency; Gain; Maintenance